Analisis Kebijakan Perkreditan Perusahaan Perbankan yang Terdaftar di Indeks LQ45 Bursa Efek Indonesia Periode November 2021 - Fajari Fauzan Hasibuan; Irvan Yoga Pardistya (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
This study examines credit policies of banking companies listed on the Indonesia Stock Exchange by comparing asset allocation for credit and asset allocation overall, using liquidity factors such as the NPL (Non-Performing Loan) ratio and LDR (Loan to Deposit Ratio) as independent variables. The secondary data used is from banking companies in the LQ45 index group from 2015-2020, and the data is analyzed using multiple linear regression to determine the effect of independent variables on the dependent variable of credit policy. Researchers uses multiple linear analysis to investigate the relationship between liquidity, represented by Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR), and credit policies of banking companies listed in LQ45 index for the period of November 2021-January 2022. The data completeness is for six years. The credit policy is measured by the percentage of allocation for credit in the asset structure of banking companies. The results show that NPL and LDR have a significant impact on credit policy with a 5% significance level, indicating the importance of credit management in banking activities.